Hemoglobin-Modified Core–Shell Fe3O4@Au Nanostructures for the Electrochemical Detection of Acrylamide - Saepudin, Endang; Yuliani, Tri; Nasution, Mochammad Arfin Fardiansyah; Khalil, Munawar; Hong, Jong Wook; Ivandini, Tribidasari Anggraningrum (UI Scholars Hub, 2021)
In this study, electrochemical detection of acrylamide using hemoglobin (Hb)-modified core–shell Fe3O4@Au nanostructures was conducted. Fe3O4 nanoparticles ( 4.9 nm) and core–shell Fe3O4@Au (5.0–6.4 nm) nanostructures were successfully synthesized by the thermal decomposition method. Electrochemical investigation revealed that the optimum amount of Hb of 2 mg/mL could be immobilized in 0.1 M acetate buffer solution (pH = 6). Moreover, the detection of acrylamide using Fe3O4@Au/Hb was evaluated by the cyclic voltammetry technique. A linear calibration curve (R2 = 0.98) in the concentration range of 0.1 to 1.0 µM could be achieved with an estimated limit of detection, limit of quantification, and sensitivity of 0.136 µM, 0.453 µM, and 0.4411 µA/µM, respectively. Furthermore, the developed biosensor exhibited high selectivity in the presence of ascorbic acid, melamine, and caffeine. The developed biosensor was applied to the detection of acrylamide in coffee samples and validated using the standard high-performance liquid chromatography (HPLC) method. The concentration of acrylamide in coffee samples was determined to be 37.450 and 35.377 ppm using electrochemical measurement and HPLC, respectively.